Phonological awareness and sinusoidal amplitude modulation in phonological dislexia - Peñaloza-López, Yolanda; Herrera-Rangel, Aline; Pérez-Ruiz, Santiago J.; Poblano, Adrián (Arquivos de Neuro-Psiquiatria, 2016)
Objective Dyslexia is the difficulty of children in learning to read and write as results of neurological deficiencies. The objective was to test the Phonological awareness (PA) and Sinusoidal amplitude modulation (SAM) threshold in children with Phonological dyslexia (PD).Methods We performed a case-control, analytic, cross sectional study. We studied 14 children with PD and 14 control children from 7 to 11 years of age, by means of PA measurement and by SAM test. The mean age of dyslexic children was 8.39 years and in the control group was 8.15.Results Children with PD exhibited inadequate skills in PA, and SAM. We found significant correlations between PA and SAM at 4 Hertz frequency, and calculated regression equations that predicts between one-fourth and one-third of variance of measurements.Conclusion Alterations in PA and SAM found can help to explain basis of deficient language processing exhibited by children with PD.
Keywords: dyslexia; phonologic dyslexia; phonologic awareness; sinusoidal amplitude modulation